Implementation of Socratic Method in online learning to enhance creative thinking: analysis review - Suhadi, S. M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Creative thinking is an aspect that should be given priority in the process of preparing a student to master higher-order thinking. It is particularly required, when an individual is in a situation to diversify the solutions of a problem to keep up with the current requirements. The process of acquiring creative thinking requires an environment that responds spontaneously for a solution. By using Socratic questioning, students will be given provocative questions to trigger spontaneous ideas along with the justification logic of each solution. The online learning environment, in which the method is employed, is indeed very conducive and suitable for teaching and learning purposes these days. In short, the role of online technology is to help students give ideas directly and spontaneously. This paper analyzed the extent to which previous studies had proven that, online learning environments which used the Socratic Method of provocation could help improve students' creative thinking.